Identifying specific cues and contexts related to bingeing behavior for the development of effective virtual environments. (1st April 2015) - Pla-Sanjuanelo, Joana; Ferrer-García, Marta; Gutiérrez-Maldonado, José; Riva, Giuseppe; Andreu-Gracia, Alexis; Dakanalis, Antonios; Fernandez-Aranda, Fernando; Forcano, Laura; Ribas-Sabaté, Joan; Riesco, Nadine; Rus-Calafell, Mar; Sánchez, Isabel; et al.
Highlights: Binge craving related situations in BN and BED are assessed. Contextual and specific cues that trigger binge craving are identified. Differences in craving between patients and controls are assessed. Development of virtual environments for cue-exposure therapy. Abstract: Background: Binge eating behavior constitutes a central feature of both bulimia nervosa (BN) and binge eating disorder (BED). Cue exposure therapy (CET) has been proposed as an effective intervention. Objective: To determine which situations and specific cues trigger higher levels of binge craving and to use the results in the development of virtual reality scenarios in which CET could be applied with BN and BED patients. Method: Participants were 101 outpatients, 50 with BED and 51 with BN, according to DSM-5 criteria, and 63 healthy undergraduate students who completed a self-administered questionnaire to assess binge craving. Results: The likelihood of binge craving in the clinical group was greater when alone at home, during the afternoon/early evening and in the late evening/at night, at weekends, and at dinner time or between meals. Higher levels of craving were produced in the kitchen, bedroom, dining room, and bakery situations. With regard to the specific cues reported, the presence of and access to high calorie food and snacks was the most commonly reported cue. Although some gender differences regarding triggering factors were obtained, no statistical differences were observed between ED subtypes. BN and BED patients showed significantly higher levels of binge craving than controls in all the contexts except when feeling positive affect; in this situation, levels of craving were low in both groups. Conclusions: This information regarding trigger contexts and specific cues can be used to create valid and reliable virtual environments for CET. Indeed, the data from this study may serve to develop a wide range of situations with different levels of binge craving, in which the therapeutic aim is to extinguish conditioned responses and facilitate the generalization of craving extinction.